Innovation In Assessment Instruments For The Hots-Based Maharah Qiroah Oral Exam At Madrasah Aliyah Al-Islam Nganjuk - Faiza Rahma, Vika; Baroroh, Umi; As-Sa’idah, Rahmah (An Naba, 2025)
This study aims to develop innovations in assessment instruments for Maharah Qiroah oral exams based on HOTS (Higher Order Thinking Skills) at Madrasah Aliyah Aliyah Al-Islam Nganjuk. Along with the development of the educational curriculum that demands critical, analytical, and creative thinking skills, an assessment is needed that not only measures memorization aspects but also the ability of students to understand, analyze, and apply qiroah knowledge. This study uses a research and development (R&D) approach with the ADDIE model in compiling HOTS-based assessment instruments. However, this study only covers the instrument development stage without involving the trial stage. The results of this study are expected to provide guidance for teachers in improving the quality of Maharah Qiroah oral exams, as well as improving students' high-level thinking skills in studying the Qur'an. In addition, this study is expected to contribute to improving the quality of education at Madrasah Aliyah Al-Islam Nganjuk